The Relevant Participation of Prolactin in the Genesis and Progression of Gynecological Cancers - Ramírez-de-Arellano, Adrián; Villegas-Pineda, Julio César; Hernández-Silva, Christian David; Pereira-Suárez, Ana Laura (Frontiers in Endocrinology, 2021)
Prolactin (PRL) is a hormone produced by the pituitary gland and multiple non-pituitary sites, vital in several physiological processes such as lactation, pregnancy, cell growth, and differentiation. However, PRL is nowadays known to have a strong implication in oncogenic processes, making it essential to delve into the mechanisms governing these actions. PRL and its receptor (PRLR) activate a series of effects such as survival, cellular proliferation, migration, invasion, metastasis, and resistance to treatment, being highly relevant in developing certain types of cancer. Because women produce high levels of PRL, its influence in gynecological cancers is herein reviewed. It is interesting that, other than the 23 kDa PRL, whose mechanism of action is endocrine, other variants of PRL have been observed to be produced by tumoral tissue, acting in a paracrine/autocrine manner. Because many components, including PRL, surround the microenvironment, it is interesting to understand the hormone’s modulation in cancer cells. This work aims to review the most important findings regarding the PRL/PRLR axis in cervical, ovarian, and endometrial cancers and its molecular mechanisms to support carcinogenesis.